Investigation of novel combination therapy for age-related macular degeneration on ARPE-19 cells - Dandamudi, Madhuri; McLoughlin, Peter; Behl, Gautam; Coffey, Lee; Chauhan, Anuj; Kent, David; Rani, Sweta; Fitzhenry, Laurence (Frontiers in Drug Delivery, 2024)
Age-related macular degeneration (AMD) is a multifactorial degenerative disease characterised by the gradual loss of central vision in individuals aged more than 50 years. There is currently no cure for this disease, but treatment can delay its progression. Consequently, there is an urgent need for the development of both new and cost-effective therapeutics. In this study, a novel combination of a corticosteroid and flavonoid was investigated on human retinal pigment epithelial cell lines to explore its potential pharmacological effect on AMD. Combination therapies, such as anti-VEGF (vascular endothelial growth factor) agents combined with photodynamic therapy and anti-VEGF agents in conjunction with corticosteroids, have been utilized previously and are known to be effective. However anti-VEGF injections are associated with serious side effects and are costly. Various disease conditions associated with AMD were stimulated on human retinal cells, which were then exposed to different concentrations of triamcinolone acetonide (TA) and quercetin (QCN) individually and in combination. This investigation aimed to assess their potential for the treatment of AMD. The combination of TA and QCN demonstrated a superior antiinflammatory effect, as TA and QCN primarily act on different inflammatory signaling pathways. Furthermore, in terms of anti-VEGF activity, both drugs exert their effects through different mechanisms: QCN inhibits kinase pathways leading to the deactivation of VEGF receptors, whereas TA destabilises VEGF mRNA, resulting in increased suppression of VEGF-C with combination treatments. The anti-oxidant assay yielded similar outcomes, demonstrating a synergetic effect when treated with combination drugs. These findings collectively suggest TA and QCN as a promising combination therapy for targeting AMD with multiple pathological conditions.